Logical meaning analysis in probe into the death of Medan Judge - Huda, Rahmat; Zuraidah, Anni; Nisma Dewi, Shoufi; Siagian, Abdul Rahman; Amri, Khairul (KnE Social Sciences, 2023)
This study focused on logico-semantic relation.Logico-semantic divided into two types; Expansion and Projection. Expansion is the relation that includes Elaboration, Extending and Enhancing in the content of language. Projection is the relation of statement in language use, namely Locution and Idea. The research design is qualitative due to the descriptive data which is in the form of words or clauses. The aim of this research is to find out the types of logical meaning and the context of the situation used in the written texts text on The Jakarta Post Newspaper.The data of the research is the clause complexes texts of The Death of Medan Judge.In analyzing the data, the technique used is Systemic Functional Linguistic (SFL) Analysis. There are sixteen (16) clauses of Extention types were found in this research as the dominant logical function. It shows that sixteen (16) from ten types of logico-semantic relations in are used in the newspaper. Keywords: Logico-semantic; SFL; systemic functional linguistic